Unriddling the Exeter riddles - Murphy, Patrick J., 1977- (Pennsylvania State University Press, 2011)
"Examines the Old English riddles found in the tenth-century Exeter Book manuscript, with particular attention to their relationship to larger traditions of literary and traditional riddling"--Provided by publisher